2010
DOI: 10.1186/1757-2215-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeling, biodistribution and gamma scintigraphy of noscapine hydrochloride in normal and polycystic ovary induced rats

Abstract: BackgroundNoscapine, an alkaloid from Papaver somniferum, widely used as an antitussive, is being clinically studied in the treatment of polycystic ovary syndrome (PCOS) and a few other cancers primarily because of its anti-angiogenesis properties. With the advent of diverse application of noscapine, we sought to determine whether the radiolabeling method can be useful in studying uptake and kinetics of the molecule in-vivo. Specific objectives of this study were to radiolabel noscapine with Technetium-99m (Tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…From another point of view, Priyadarshani et al 14 reported successful action of noscapine in the amelioration of PCOS. Noscapine is a plant alkaloid that serves as a cough suppressant.…”
Section: Current Understanding Of the Pathogenesis Of Pcosmentioning
confidence: 99%
“…From another point of view, Priyadarshani et al 14 reported successful action of noscapine in the amelioration of PCOS. Noscapine is a plant alkaloid that serves as a cough suppressant.…”
Section: Current Understanding Of the Pathogenesis Of Pcosmentioning
confidence: 99%
“…Preclinical biodistribution and pharmacokinetics data for investigational agents are routinely obtained in animal studies using radiolabeled materials [6] . Many of these studies employ post-mortem scintillation counting of the labeled radioactivity in excised organs and tissues [7] , [8] . Additional understanding of the kinetic changes in biodistribution has generally required either the sacrifice of multiple animals at multiple time points or the use of non-invasive nuclear imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies show that alkaloids obtained from Papaver species could not only be used as analgesic or sedative but also in other areas such as cancer treatment [12]. P. somniferum L. alkaloids that show promise in cancer treatment include noscapine, which interacts with α-tubulin and has anticancer and antiangiogenetic properties [13,14]; codeinone, an oxidative product of codeine which has apoptotic effects through fragmentation of DNA [15]; morphine, which shows anticancer activities by inhibiting NF-κB; and (-)-3-acetyl-6β-(acetylthio)-N-(cyclopropyl-methyl)-normorphine (KT-90), a derivative of morphine [16]. To the best of our knowledge, pharmacological effects of P. somniferum L. extracts on HT29, HeLa, C6 cancer cell lines and Vero normal cell lines have not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%